Determinan Kejadian Hipertensi pada Masyarakat Pedesaan di Wilayah Kerja Puskesmas Simarmata Kecamatan Simanindo Kabupaten Samosir 2024 - Sibarani , Melda; Siagian, Mindo Tua; Anita , Surya; Dachi , Rahmat Alyakin; Tarigan, Frida Lina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Hypertension is a major global health issue and a significant risk factor for cardiovascular and renal diseases. Data from the Samosir Regency Health Office in 2022 indicated a high prevalence of hypertension (30%) among adults in Simanindo District, highlighting a critical local public health concern. Objectives: This study aimed to identify the determinants associated with the incidence of hypertension in the working area of the Simarmata Public Health Center, Simanindo District, Samosir Regency. Methods: A quantitative study with a cross-sectional design was conducted. A sample of 95 respondents was selected proportionally from four villages. Data on Body Mass Index (BMI), alcohol consumption, smoking habits, and dietary patterns were collected through interviews and measurements. Data analysis employed the Chi-square test and multivariate logistic regression. Results: The study revealed significant relationships between hypertension and BMI (p=0.000), alcohol consumption (p=0.000), smoking habits (p=0.000), and dietary patterns (p=0.018). Multivariate analysis identified smoking habit as the most dominant factor, with smokers having 9.758 times higher odds of developing hypertension (Exp(B) = 9.758; 95% CI: 2.697–35.303). Conclusion: Smoking habit is the most dominant determinant of hypertension in this community. It is recommended that the head of the Simarmata Public Health Center enhance the role of health workers in providing health education, particularly on the dangers of smoking and its impact on hypertension, to reduce its incidence.